Radiological outcome analyses of transtrochanteric posterior rotational osteotomy for osteonecrosis of the femoral head at a mean follow-up of 11 years - Zhao, Garida; Yamamoto, Takuaki; Motomura, Goro; Iwasaki, Kenyu; Yamaguchi, Ryosuke; Ikemura, Satoshi; Iwamoto, Yukihide (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2013)
This study investigated the radiological factors that correlated with progression of collapse and joint space narrowing after transtrochanteric posterior rotational osteotomy (PRO) for osteonecrosis of the femoral head. This study reviewed 51 hips in 47 patients with a mean follow-up of 11years (5–20). The subjects included 29 males and 18 females with a mean age of 34years (12–54) at the time of surgery. The 51 hips were divided into two groups based on the radiological outcome (group I: evidence of progression of collapse and/or joint space narrowing, group II: no evidence of either progression of collapse or joint space narrowing). Both clinical and radiological factors were analyzed by both univariate and multivariable analyses. Six hips were categorized as group I and 45 hips were categorized as group II. The postoperative intact ratio and preoperative stage were significantly correlated with the radiological outcome in both univariate (P<0.0001, P=0.006) and multivariate (P=0.0014, P=0.0039) analysis. The cutoff point for the postoperative intact ratio (the minimum ratio required to prevent both progression of collapse and joint space narrowing) was 36.8%. The results of this study indicate that the postoperative intact ratio is one of the main influences on progression of collapse and/or joint space narrowing after PRO, and should be at least 36.8%. An increased awareness of this critical ratio would be useful for planning the optimal use of this procedure.